Odpowiedzi

2009-11-19T14:25:29+01:00
1.

9x+y=33 / - 9x
5x-2y=26

y=33 - 9x
5x - 2y= 26

y=33-9x
5x - 2(33-9x)=26

y=33-9x
5x - 66+ 18x=26

y=33-9x
-13x = 26+66

y=33-9x
-13x=91 / : (-13)

y=33-9x
x = 7

y = 33 - 9*7
x=7

y= 33 - 63
x=7

y = -30
x=7


2.
2009-11-19T14:44:29+01:00
Zad.1
9x+y=33
5x-2y=26

y=33-9x
5x-2(33-9x)=26

y=33-9x
5x-66+18x=26

y=33-9x
23x=26+66 /:23

y=33-9x
x=4

y=-3
x=4

zad.3
6x+7y=3
2x+5y=1

6x+7y=3
2x=1-5y /:2

6x+7y=3
x=0,5-2,5y

6(0,5-2,5y) +7y=3
x=0,5-2,5y

2-15y+7y=3
x=0,5-2,5y

-8y=3-2 /:(-8)
x=0,5-2,5y

y=-0,125
x=0,5-2,5*(-0,125)

y=-0,125
x=O,1875 ?

zad.4
2x+2/3y=44
3x-5/6y=33

2x=44-2/3y /:2
3x-5/6y=33

x=22-3y
3(22-3y)-5/6y=33

x=22-3y
66-9y-5/6y=33

x=22-3y
-59/6y=33-66 /:-59/6

x=22-3y
y=... ?